1957
DOI: 10.1136/bmj.1.5033.1437
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ulcerative Colitis with Local Hydrocortisone Hemisuccinate Sodium

Abstract: TOXIC EFFECTS OF IPRONIAZID BRrrsHMEDICAL JOURNAL within 36 hours. He continued on the same dose of iproniazid for a further five months, during which time he showed signs of increasing restlessness, euphoria, insomnia, and other mild toxic effects. He died in coma after an acute illness characterized by fever, coarse tremor, hallucinations, and " auditory delusions." At necropsy the brain showed that death was due to haemorrhagic encephalitis; since no other cause was apparent this was believed to be due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1958
1958
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Local corticosteroid treatment began to be used in 1955 but was at first confined to selected mild or moderate cases (Truelove, 1956(Truelove, , 1957. When subsequent controlled trials had shown it to be beneficial in such cases (Truelove, 1958;Watkinson, 1958) it began to be used more extensively but its use in severe attacks of the disease did not begin until 1957. Subsequently the combined use of systemic and local corticosteroid treatment was found to.…”
Section: Discussionmentioning
confidence: 99%
“…Local corticosteroid treatment began to be used in 1955 but was at first confined to selected mild or moderate cases (Truelove, 1956(Truelove, , 1957. When subsequent controlled trials had shown it to be beneficial in such cases (Truelove, 1958;Watkinson, 1958) it began to be used more extensively but its use in severe attacks of the disease did not begin until 1957. Subsequently the combined use of systemic and local corticosteroid treatment was found to.…”
Section: Discussionmentioning
confidence: 99%
“…Pancolitis was induced with 40/o acetic acid. Animals were then randomised to receive oral therapy for 72 hours with (1) budesonide-3-D-glucuronide, (2) free budesonide, or (3) vehicle. Drug efficacy and colitic healing was determined by measuring gross colonic ulceration, myeloperoxidase activity, and in vivo colonic fluid absorption.…”
mentioning
confidence: 99%
“…Topical treatment of colitis with corticosteroids Steroids were first used topically in colitis by Truelove in 1956 and their value in distal disease confirmed by a series of controlled trials (Truelove, 1958;Watkinson, 1958Watkinson, , 1961aMatts, 1960Matts, , 1962Matts & Gaskell, 1961;Patterson et al 1965). The major attractions of this method of treatment are that minimal or no side-effects develop, and it is possible to obtain much higher concentrations of steroid locally than could be achieved by systemic therapy.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Freshly prepared hydrocortisone hemisuccinate sodium can be administered by rectal drip, may penetrate to the right colon and have a beneficial effect in 52-69% of the patients treated (Truelove, 1958;Patterson et al, 1965;Watkinson, 1961a). The stability of prednisolone 21phosphate enabled it to be administered from disposable enema bags as a retention enema and remission rates of 75-88 % were claimed in patients with distal disease (Matts & Gaskell, 1961;Patterson et al, 1965;.…”
Section: Corticosteroidsmentioning
confidence: 99%